People’s Satisfaction towards Public Service of Maha Sarakham Provincial Administrative Organization Fiscal Year 2022 - Soonthorn, Sitthiporn; Saiyaros, Ratchanida; Boonruan, Sathitkoon; Khamwisettanathon, Thantikan; Thammarat, Sodsai; Noicharoen, Phunthila (Interdisciplinary Academic and Research Journal, 2022)
Providing good public services, local government organizations should be organized in the form of commercial and social enterprises, in which a good local public service organization should have four dimensions, namely; The suitability of the public service type, the degree of exploitation and exploitation, the person or audience of public service, and the correspondence between the public service type and the public service model. Therefore, this research had objectives were 1) to study the level of people’s satisfaction towards the public service of the Maha Sarakham Provincial Administrative Organization, 2) To study the relationship between personal factors and public services of the Maha Sarakham Provincial Administrative Organization, 3) to study the recommendations for the management of the Maha Sarakham Provincial Administrative Organization. This research was held in Fiscal Year 2022. The sample consisted of 400 people. The research instrument was a questionnaire. The statistics were frequency, percentage, mean, standard deviation, and Pearson’s Product Moment Correlation Coefficient. The finding found that: (1) People’s Satisfaction towards Public Service of Maha Sarakham Provincial Administrative Organization, the number of 4 projects as overall at the highest level accounted for 93.80%, classified as work, found that they were satisfied At the highest level in every job. (2) The results of the analysis of the relationship between personal factors and public service of the Maha Sarakham Provincial Administrative Organization, the overall positive correlation was at a low level of 0.475. And (3) People’s recommendations for the public service of the Maha Sarakham Provincial Administrative Organization are as follows: The staff should be friendly, facilitating the service to the recipient must be based on friendliness, should arrange staff who have basic treatment knowledge and readiness to work, The staff should have the right attitude to serve, service that impresses the recipient. And there should be a systematic setup of a service center and data warehouse.